2021
DOI: 10.3934/math.2022045
|View full text |Cite
|
Sign up to set email alerts
|

Existence results for coupled system of nonlinear differential equations and inclusions involving sequential derivatives of fractional order

Abstract: <abstract><p>In this article, we investigate new results of existence and uniqueness for systems of nonlinear coupled differential equations and inclusions involving Caputo-type sequential derivatives of fractional order and along with new kinds of coupled discrete (multi-points) and fractional integral (Riemann-Liouville) boundary conditions. Our investigation is mainly based on the theorems of Schaefer, Banach, Covitz-Nadler, and nonlinear alternatives for Kakutani. The validity of the obtained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…e boundary value problems of fractional order, in particular, garnered much attention. See [12][13][14][15][16][17][18][19] for the most recent results on FDEs with multipoint and integral boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…e boundary value problems of fractional order, in particular, garnered much attention. See [12][13][14][15][16][17][18][19] for the most recent results on FDEs with multipoint and integral boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have also examined coupled systems of di erential equations of fractional order. ese systems naturally exist in a wide variety of real-world circumstances [19][20][21][22]. A series of papers [19,20,[23][24][25][26][27] and the sources listed therein contain some recent results on this subject.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of turbulent fluid flows, control theory, blood flow through biological tissues, porous media, and signal and image processing, among other fields, have all benefited greatly from the use of fractional calculus. The recent study on fractional calculus, including theory and applications, can be found in [1][2][3][4][5][6][7][8][9][10][11][12][13]. Their research is especially pertinent since coupled systems with fractional differential equations are used to address a wide range of real-world problems.…”
Section: Introductionmentioning
confidence: 99%